Dynamic PSMA total-body PET/CT in prostate cancer: technical principles and clinical potential - Yongkang Shuai; Irene Brusa; Riccardo Mei; Stefano Fanti (Clinical and Translational Imaging, 2026)
Abstract Background The incidence of prostate cancer continues to rise worldwide. While conventional static PET/CT provides semi-quantitative metrics, total-body PET/CT enables voxel-level dynamic imaging and parametric imaging, demonstrating great potential for clinical applications in prostate cancer. Therefore, this review synthesizes the technical principles of dynamic PSMA total-body PET/CT and its emerging clinical applications in prostate cancer, providing a novel clinical insight for individualized patient management. Methods We performed a state-of-the-art narrative review of dynamic PSMA total-body PET/CT in prostate cancer, searching the PubMed database up to March 2026. Our analysis focused on the methodology of PSMA kinetic modeling and parametric reconstruction, alongside their clinical applications across clinical staging, treatment response monitoring, and individualized radioligand therapy dosimetry in prostate cancer. Results Dynamic PSMA total-body PET/CT advances molecular imaging from semi-quantitation to absolute quantification through non-invasive image-derived input function extraction and kinetic modeling. Clinically, this absolute quantification effectively suppresses background activity, improving diagnostic accuracy in prostate cancer staging and recurrence. Furthermore, dynamic imaging offers novel insights for early treatment response assessment and provides a quantitative basis for dosimetric evaluation in individualized radioligand therapy. To address prolonged acquisition times, deep learning and modified kinetic models have compressed scan durations into clinically acceptable windows, improving tolerability and mitigating motion artifacts. Conclusions Dynamic PSMA total-body PET/CT bridges kinetic modeling with precision oncology, representing a technological evolution from conventional semi-quantitation to absolute quantification. Despite its early clinical promise, the technology’s widespread translation depends on rigorous prospective validation across different clinical scenarios. Ultimately, routine clinical adoption of dynamic total-body PSMA PET/CT requires resolving its current technical constraints and definitively proving its added value over standard static PET/CT in patient management.